The network science approach in determining the intellectual structure, emerging trends and future research opportunities: an application to senior tourism research - Pestana, M.H.; Vargas-Sánchez, A.; Moutinho, L. (Tourism Management Perspectives, 2019)
This study applies bibliometric analysis to senior tourism research from 1998 to 2017, identifies its intellectual structure, emerging trends, and future research opportunities. Data collected from the Web-of-Science and Scopus is used to build an expanded network encompassing 700 core articles and 7,221 citations. The results reveal a slowly increasing growth of research, with the last period including 41% of outputs. The most cited papers are mainly older, represent 1.99% of the sample and account for 8.52% of citations. The network of journals and institutions show the highest ranking to be in Tourism Management and in the University of Queensland. The identification of structural holes, critical articles and the keyword analysis highlights priorities in senior tourism, pointing to new opportunities for research. The dynamic analysis of the last two decades using CiteSpace for co-citation and co-occurrence network analysis aims to equip researchers and the hospitality industry with new exploration tools.